Phenotypic and genotypic characterization of antibiotic-resistant bacteria from Swiss ready-to-eat meat products - Thoenen, Lisa; Hummerjohann, Joerg; Schwendimann, Livia; Marti, Elisabet (Frontiers in Microbiology, 2025)
Antimicrobial resistance is a global health concern, which is partly driven by rising meat consumption, which has led to the intensive farming of livestock that relies on antibiotics. ready-to-eat animal products can carry antibiotic-resistant bacteria, posing risks to humans since they are often consumed without further cooking. While countries such as Switzerland limit antibiotic use in agriculture, contamination of meat with antibiotic-resistant bacteria can still occur during meat processing, and non-antibiotic agents such as heavy metals may contribute to the co-selection of resistance. This study aimed to characterize antibiotic-resistant bacteria in ready-to-eat meat products from various Swiss butcheries. Presumptive resistant bacteria were isolated using selective plating and analyzed phenotypically and genotypically. A total of 53 bacteria-antibiotic resistance combinations were identified, including Enterobacterales resistant to third-generation cephalosporins, vancomycin-resistant Enterococci, and one strain of methicillin-resistant Staphylococcus aureus. Of the 804 products sampled, 177 antibiotic-resistant bacteria were isolated, 148 of which showed multidrug resistance. Notably, these strains remained susceptible to last-resort antibiotics such as carbapenems and colistin. Whole-genome sequencing of 31 selected isolates revealed 164 antibiotic resistance genes spanning 25 classes, confirming resistance to beta-lactams, cephalosporins, and tetracyclines. We also detected genes conferring resistance to metals, suggesting co-selection pressures. Long-read sequencing revealed that the majority of the antibiotic resistance genes were chromosomal, while others were plasmid-encoded, indicating the potential for horizontal gene transfer. This study demonstrates that ready-to-eat meat products are reservoirs of antibiotic and metal resistance genes, as well as antibiotic-resistant bacteria, even at low levels. From a One Health perspective, our results highlight the importance of extending AMR surveillance across the food chain and underscore the need to include non-traditional bacterial indicators.